Public opinions and attitudes toward a state monopoly: a study of the finnish gambling system - Macey Joseph R.; Abarbanel Brett L.; Castrén Sari; Hamari Juho J.; Salonen Anne H. (BioMed Central Ltd, 2025)
Background Gambling regulated through a state monopoly is often justified for reasons of public health, that is, that monopolies are a more effective means of reducing potential harm. This focus on harm prevention has increased in recent years, particularly as a result of pressures arising from the growth of online gambling and of legislation designed to promote competition. While prior works have examined the role of stakeholders in influencing policy decisions and in public discussions of the monopoly systems, attention has been focused on those with direct financial interests; the opinions of the public have largely been absent from these discussions. In 2017 Finland restructured its monopoly order to improve efficacy of addressing gambling related harms; this restructuring offers a valuable insight into public perceptions of and attitudes toward the suitability of the Finnish system to address gambling-related harm.
Methods This work uses Structural Equation Modelling and compares attitudes toward the Finnish system between 2015 (pre-restructuring) and 2019 (post-restructuring).
Results Overall public opinion of the Finnish system as being suitable for addressing gambling harms declined between 2015 and 2019, despite the restructuring. Several predictors of attitudes were identified, however, the majority had small effect sizes, while the model explained little variance.
Conclusion This work concludes that existing approaches to examining public opinions of gambling regulation should be amended to include additional predictors. Furthermore, it is likely that context-specific predictors should be included in models, in order to reflect the socio-cultural history of the population being investigated. Such predictors should be determined in respect to the population of interest but, for example, could include items measuring trust in authority, political orientation, cultural acceptance of gambling, or religious affiliation.